Cidade e política sobre drogas : desafios da reforma psiquiátrica no contemporâneo - Clemente, Anselmo (2014)
In the context of psychiatric reform, this research concerns the attention to drug users, particularly "crack users" who live in metropolitan areas. The overall debate looks into the formation of the city by taking urban life into consideration. In that sense, the conflict between the public and the private spheres, the governmentality of human bodies within the ´urbe´, as well as the serialization of contemporary life emerge in the care provided in mental health services. The present dissertation is organized into three scientific chapters, one of which written in literary style in order to address the production of subjectivity in the city. The context in which the research is developed touches the experience of a local mental health institutional network in its consolidation and tensions. The present research also expands to report the experience on the international stage of care provided to drug users in Portugal, in reference to international organizations in the area. Finally, the conclusion brings forth the developmental urban process experienced in the final years of the nineteenth and of the twentieth century as well as the subsequent exclusion of deviants of social life via mental hospitals, taking as example the city of Rio de Janeiro.